A hybrid GRASP-VNS for ship routing and scheduling problem with discretized time windows. (October 2015) - de Armas, Jesica; Lalla-Ruiz, Eduardo; Expósito-Izquierdo, Christopher; Landa-Silva, Dario; Melián-Batista, Belén
Abstract: This paper addresses the Ship Routing and Scheduling Problem with Discretized Time Windows. Being one of the most relevant and challenging problems faced by decision makers from shipping companies, this tramp shipping problem lies in determining the set of contracts that should be served by each ship and the time windows that ships should use to serve each contract, with the aim of minimizing total costs. The use of discretized time windows allows for the consideration of a broad variety of features and practical constraints in a simple way. In order to solve this problem we propose a hybridization of a Greedy Randomized Adaptive Search Procedure and a Variable Neighborhood Search, which improves previous heuristics results found in the literature and requires very short computational time. Moreover, this algorithm is able to achieve the optimal results for many instances, demonstrating its good performance.